Membrane aerated biofilm reactor in recirculating aquaculture system for effluent treatment - Almeida, Juliana Cristina Ribeiro [UNESP]; Bega, João Miguel Merces; Leite, Luan de Souza; de Oliveira, Jefferson Nascimento [UNESP]; Albertin, Liliane Lazzari [UNESP]; Matsumoto, Tsunao [UNESP] (Taylor & Francis, 2022)
The implementation of fish farming has been increasing worldwide over the last decades, as well the search for alternative production systems and the treatment of their generated effluent. Recirculating Aquaculture System (RAS) is a compact solution for future intensive fish farming. However, few configurations of treatment technologies were tested in RAS, such as systems with a Membrane Aerated Biofilm Reactor (MABR). In this scene, this study aimed to evaluate the RAS effluent treatment efficiency device for intensive Nile tilapia (Oreochromis niloticus) production, the fish species most cultivated worldwide. The novel RAS configuration was composed of a cultivation tank (CT), a Column Settler, and a MABR. The RAS performance was evaluated by pH, temperature, turbidity, dissolved oxygen (DO), total nitrogen (TN), ammonia, nitrite, nitrate, total solids (TS), and chemical oxygen demand (COD). The obtained results in average values for temperature, pH, and DO inside the CT were 25.22 ± 1.88°C, 7.61 ± 0.33, and 3.80 ± 1.30 mg L−1, respectively, as ideal for tilapias survival. Average removal efficiencies found in the RAS for turbidity, COD, TN, nitrite, nitrate, ammonia, and TS were 50.0, 40.5, 11.7, 40.2, 13.1, 35.0, and 11.4%, respectively. Overall, we observed removals for all parameters studied, with good results, particularly, for COD, turbidity, nitrite, and ammonia. The evaluated system proved an effective alternative for water reuse in RAS capable of maintaining water quality characteristics within the recommended values for fish farming.
Keywords: ammonia; Column settler; fish farming; Nile tilapia; wastewater treatment